Analysis of blood pressure wave in the human common carotid artery on the basis of non-invasive ultrasonic examinations - POWAŁOWSKI, T. (Archives of Acoustics, 2000)
The aim of the study was the examination of the forward and reflected blood pressure waves in the common carotid artery on the basis of non-invasive ultrasonic examinations. The study concerned the effect of stenosis of the internal carotid artery caused by atherosclerosis on the mean reflection coefficient modulus and the time delay between the reflected blood pressure wave and the forward blood pressure wave. The investigations were carried out on a group of healthy persons (30 cases) and on a group of sick persons (17 cases) with stenosis or occlusion of the internal carotid artery.